Politics Minority Identity: A Discourse Analysis On Social Media Between Indonesia And Singapore - Nur Sofyan; Naili Farida; Abi Pranaya Tyaswara (Master of Communication Science Program, Universitas Diponegoro, 2026)
This study explores the impact of media narratives on the political identities of Muslim minorities in Bali, Indonesia, and Singapore. Examining Muslim minorities in these two settings is particularly compelling because they represent contrasting contexts, with Muslims forming a religious minority in Hindu-majority Bali and an ethno-religious minority in multicultural Singapore. While extensive research exists on identity politics, there is limited focus on how media narratives shape minority identities within the context of political competition. This study examines how media portrayals of Muslim minorities influence political contestation, particularly in election campaigns. Using a qualitative approach, the research analyzes online news content through Critical Discourse Analysis (CDA) and Social Network Analysis (SNA) to identify narrative patterns. Additionally, a descriptive method is applied to understand the distribution of these narratives on social media. Existing studies indicate that minorities are often underrepresented or negatively portrayed in mainstream media, including news and entertainment. However, such portrayals do not entirely exclude ethnic minorities from political participation. By analyzing both news media and social media, this study contributes to the political marketing literature by providing new insights into the role of media narratives in shaping electoral dynamics for Muslim minorities in Bali and Singapore